Strengthening Community Capacity To Face Drought With Rainwater Harvesting Technology - Kurnia Hartati, Fadjar; Sucahyo, Bambang Sigit; Putra, Angga Pratama (Salus Publica: Journal of Community Service, 2023)
Kalanganyar Village is a village located at the easternmost tip of Sidoarjo Regency, East Java. This village makes a major contribution to the field of aquaculture and processing. However, in the rainy season, this village experiences inundations and even floods in some areas, and during the dry season experiences drought or difficulty getting clean water. Based on this, this Community Service activity aims to help provide solutions by applying Rainwater Harvesting technology. The method used in this activity begins with permits in related agencies, then planning, counseling, practice making rainwater harvesting installations, and evaluations are carried out. With this activity, the Kalanganyar Village Community can make RHT installations independently after this activity, there are no inundations and floods in the rainy season, in the dry season clean water needs are still met, and the Kalanganyar Village community has been able to increase their capacity in dealing with drought to prevent non-natural disasters